Pengembangan Metode Pembelajaran Berbasis Permainan pada Mata Kuliah Agama Islam di AKN Putra Sang Fajar Blitar Menggunakan Model 4-D Thiagarajan - Muluk, Muchamad Saiful; Athaillah, Ibnu (MA'ALIM: Jurnal Pendidikan Islam, 2023)
Learning theoretical subjects at Vocational Colleges (PTV) is very identical to practice, but has its own challenges, including the general basic subjects (MKDU) of Islamic Religion. The problem with Islamic religious education in higher education, apart from the curriculum, teacher competency, differences in the quality of student understanding, and scientific dichotomy, is that there is also a very small learning portion (around 2 credits) from other subjects. This condition requires creative innovation, one of which is the development of game-based learning. This research focuses on developing a game-based learning method with Thiagarajan 4D model on Muslim Personality material which consists of 4 stages, namely defining, designing, developing and disseminating. Research data was collected by interviews, observation and documentation. The design of this game-based learning method has been validated by material and game experts, tested on a small scale and implemented in classrooms. Based on the validation results from material experts and game experts, the results showed that game-based learning designs are very suitable for use. The results of small-scale trials and implementation in classrooms show that students are enthusiastic, actively discussing, asking and answering, confident, and eager to participate in learning without feeling sleepy. Game-based learning methods can be used as an effective way to teach theory courses.